KEDUDUKAN HUKUM INTERNASIONAL SEBAGAI BAGIAN DARI PENGANTAR HUKUM DI INDONESIA - Devirianti Effendi; Yenni Fitria; Maria Margaeta Hutajulu (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The position of international law as part of legal education in Indonesia is crucial in understanding the dynamics of the national legal system, which is increasingly open to global norms. This study employs a normative legal research method, which is juridical-dogmatic in nature, analyzing legislation, legal doctrines, court decisions, and academic literature as primary sources. The research focuses on the status of international law within Indonesia’s domestic legal hierarchy, particularly within the constitutional framework of the 1945 Constitution, as well as its application in legal practice such as treaty ratification and the use of international law in judicial decisions. The findings indicate that international law holds a strong position in Indonesia’s legal system, serving not only as a source of law but also as an interpretive tool for domestic law, especially in areas such as human rights, environmental law, and criminal law. Indonesia’s adoption of the monist principle allows international law to be directly applicable without the need for formal transformation, provided certain conditions are met. Therefore, integrating international law into introductory legal education in Indonesia is not only relevant but also essential in fostering a globally oriented legal awareness. Understanding international law provides a fundamental basis for law students to face legal challenges in the era of globalization.Keywords: International Law, Introduction to Legal Science, National Law, Indonesia.